2018
DOI: 10.1289/ehp3189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prenatal Exposure to Bisphenol Analogues on Development and Long-Term Health of the Mammary Gland in Female Mice

Abstract: Background:Continued efforts to phase out bisphenol A (BPA) from consumer products have been met with the challenges of finding safer alternatives.Objectives:This study aimed to determine whether early-life exposure to BPA and its related analogues, bisphenol AF (BPAF) and bisphenol S (BPS), could affect female pubertal mammary gland development and long-term mammary health in mice.Methods:Timed pregnant CD-1 mice were exposed to vehicle, BPA (0.5, 5, 50mg/kg), BPAF (0.05, 0.5, 5mg/kg), or BPS (0.05, 0.5, 5mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 93 publications
1
70
0
Order By: Relevance
“…As in the mouse model, some effects of BPA are not similar to those of estrogens, for example, inhibition of ductal growth at puberty (Markey et al 2001;Muñoz-de-Toro et al 2005), enhanced ductal growth during fetal life (Vandenberg et al 2007;Speroni et al 2017), others are clearly estrogen-like, such as the increased score at PND90P reported here and the accelerated expression of lateral branching in the mouse (Muñoz- de-Toro et al 2005). There are also other effects seemingly unrelated to estrogenicity; changes in the stromal fraction of the gland and inflammatory cell responses that have been noted in response to developmental BPA exposures (Tucker et al 2018;Wadia et al 2013).…”
Section: Cancer: This Study and The Core Studysupporting
confidence: 53%
“…As in the mouse model, some effects of BPA are not similar to those of estrogens, for example, inhibition of ductal growth at puberty (Markey et al 2001;Muñoz-de-Toro et al 2005), enhanced ductal growth during fetal life (Vandenberg et al 2007;Speroni et al 2017), others are clearly estrogen-like, such as the increased score at PND90P reported here and the accelerated expression of lateral branching in the mouse (Muñoz- de-Toro et al 2005). There are also other effects seemingly unrelated to estrogenicity; changes in the stromal fraction of the gland and inflammatory cell responses that have been noted in response to developmental BPA exposures (Tucker et al 2018;Wadia et al 2013).…”
Section: Cancer: This Study and The Core Studysupporting
confidence: 53%
“…Like in the mouse model, some effects of BPA are not similar to those of estrogens, for example, inhibition of ductal growth at puberty (Markey et al 2001;Munoz de Toro et al 2005), enhanced ductal growth during fetal life Speroni et al 2017), others are clearly estrogen-like, such as the increased score at PND90P reported here and the accelerated expression of lateral branching in the mouse (Munoz de Toro et al 2005). There are also other effects seemingly unrelated to estrogenicity; changes in the stromal fraction of the gland and inflammatory cell responses which have been noted (Tucker et al 2018;Wadia et al 2013) in response to developmental BPA exposures.…”
Section: Cancer: This Study and The Core Studymentioning
confidence: 66%
“…Alterations in ductal elongation at puberty and lateral branching and budding during adulthood were attributed to altered responses to mammotropic hormones Ayyanan et al 2011). Recent studies confirmed that developmental exposures to other BPA related substances (BPS and BPAF) in mice also induce precocious development of the mammary epithelium, and increased epithelial lesions and mammary tumors in adulthood (Tucker et al 2018). However, these results were obtained in the mouse, which is not considered as good a model for mammary cancer as the rat.…”
Section: Cancer: This Study and The Core Studymentioning
confidence: 95%
“…The mid dose (200 μg BPS/kg/day) was selected based on prior studies showing that this dose disrupted maternal behaviors, the lactating mother, and development of the mammary gland [2] , [4] , [5] . The highest dose (2000 μg BPS/kg/day) was selected based on results from a recent study at the National Toxicology Program which revealed significant effects of BPS on the female mammary gland at a similar dose (5000 μg/kg/day) [6] . Doses were adjusted daily for body weight.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%